2019
DOI: 10.1108/jhr-07-2018-0062
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge about oral cancer in Uganda: a free dental camp experience

Abstract: Purpose The purpose of this paper is to assess the levels of awareness and knowledge about oral cancer, its causes and or risk factors among Ugandan patients seeking oral healthcare. Design/methodology/approach This was a cross-sectional study on adult patients who attended a free dental camp. An assistant-administered questionnaire either in English or Luganda was provided to every even-numbered registered adult who consented to participate in the study. Information on demographics and known risk factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
2
0
2
Order By: Relevance
“…More than half of the population in this study recognizes the existence of oral cancer (58.6%), a finding that agrees with several studies worldwide ( 5 - 9 , 13 - 15 ) with percentages of knowledge ranging between 22% and 94%. Although it is lower than reported in some countries, the level or depth of knowledge is low.…”
Section: Discussionsupporting
confidence: 92%
“…More than half of the population in this study recognizes the existence of oral cancer (58.6%), a finding that agrees with several studies worldwide ( 5 - 9 , 13 - 15 ) with percentages of knowledge ranging between 22% and 94%. Although it is lower than reported in some countries, the level or depth of knowledge is low.…”
Section: Discussionsupporting
confidence: 92%
“…Preocupantemente, somente pouco mais da metade dos escolares desta pesquisa consideraram o cigarro como principal fator de risco para o câncer de boca, revelando uma importante deficiência na relação entre o conhecimento científico existente e a conscientização da população. Outros estudos encontraram resultados semelhantes ou ainda piores aos observados nesta pesquisa e sugerem que estratégias de saúde pública mais elaboradas, incluindo o uso de mídias sociais, jornais, rádio, televisão, e atuação de lideranças e representantes de comunidades podem ser úteis como estratégia para que as informações atinjam, de forma compreensível e adequada, os diferentes estratos populacionais 18,19 .…”
Section: áLcool E Vírusunclassified
“…Moreover, factors like smoking, untreated oral disease, alcohol, and HPV contribute more to the burden of OC in different regions of the world [9,15], but, in the Eastern region of Africa, Uganda was ranked high in global alcohol consumption, and it is catching up on tobacco product use. So, this indicates that there is a high incidence of OC cases in the Eastern African countries [16]. Additionally, previous studies reported that two thirds of patients with OC are diagnosed at an advanced stage of OC, and this indicates that the delay may lead to a high mortality and morbidity [17].…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, previous studies reported that two thirds of patients with OC are diagnosed at an advanced stage of OC, and this indicates that the delay may lead to a high mortality and morbidity [17]. Although the OC has been highly prevalent in Asia, this disease has also been a public health burden in the Eastern Africa, such as in Kenya, Uganda, and Tanzania, where its prevalence varies from 2 to 3.6% [16,18,19]. Smoking alone has claimed an estimated 71% of lives that died and were diagnosed with OC in developed countries against about 37% in LMICs [11].…”
Section: Introductionmentioning
confidence: 99%